Juvenile Onset Clinically Amyopathic Dermatomyositis Presenting as Calcinosis Cutis - Verma, Kuldeep; Gupta, Mudita; Thakur, Saru (Journal of Enam Medical College, 2018)
Dermatomyositis (DM) is an autoimmune inflammatory disorder characterized by involvement of muscles and skin. Classical dermatomyositis (CDM) patients display the hallmark cutaneous manifestations of dermatomyositis (DM), proximal muscle weakness, and laboratory evidence of myositis. Rarely, DM presents with cutaneous features of the disease without muscle involvement for a period of more than six months. Such cases are classified into a category of clinically amyopathic dermatomyositis (CADM) which includes amyopathic DM and hypomyopathic DM. We present a case of a 14-year-old child who presented with calcinosis cutis and cutaneous findings suggestive of the disease without muscle involvement. The child was diagnosed as a case of juvenile onset CADM. J Enam Med Col 2018; 8(2): 101-104